Looking at the Spread of Precarious Employment Researches: A Literature Review - Purnomo, Joko Hadi; Hidayati, Niswatin Nurul (LP2M UIN KH.Achmad Siddiq Jember, 2024)
The globalization of economies has ensured that precarious work is a fast-emerging feature of many contemporary labor markets. Precarious work is essential to study because it impinges on workers' rights, economic stability, and social welfare. While previous works researched the effects of precarious employment, they often needed to address these themes and their trends for an overall outlook of how precariousness seems to come together in discourse. This paper intends to fill the gap by systematically applying a new data visualization tool called VOS Viewer to review related literature. Specifically, the study tries to map the network of articles, key themes, prolific authors, and new trends, especially on precarious employment. The nature of the research was qualitative, and the available literature on the research trends in the world currently and their gaps were analyzed. Results indicate precarious employment with Covid-19, climate change, gender issues, poverty, and mental health. Moreover, in the Indonesian context, connections are drawn to commodification, COVID-19, and community resilience; this indicates significant gaps and points to ample avenues for further research. Precarious employment needs further in-depth exploration beyond the well-researched areas, especially in Indonesia, to grapple with the challenges posed by such an evolving employment landscape.